PENERAPAN SISTEM INFORMASI PELAPORAN KEUANGAN PADA TOKO SUN COMPUTER BALI - Nirwana, Ni Kade Ayu; Dirgayusari , Ayu Manik; Karvana , Ketut Gde Manik; Pratiwi , Ni Wayan Anggita Dara (ASOSIASI IDEBAHASA KEPRI, 2025)
A financial reporting information system is essential for supporting the smooth operation of businesses, including Sun Computer Bali. This research aims to design a system that addresses unstructured and non-integrated income and expenditure records. The current financial reports are limited to daily summaries, lacking details on debits, credits, receivables and payables. Furthermore, store owners and employees face difficulties monitoring stock, increasing the risk of stock loss due to the absence of real-time inventory tracking. The proposed system produces comprehensive monthly financial reports, enables real-time inventory monitoring, supports decision-making, improves operational efficiency, and simplifies the tracking of profits and losses. The system design adopts the Waterfall method, utilizing the Laravel Framework for development and MySQL for database management. System testing was conducted through user interviews to evaluate functionality, while the DeLone and McLean Information System Success Model was used for evaluation. Results indicate that the financial reporting information system effectively meets user needs, particularly in generating structured financial reports and monitoring inventory. This system significantly enhances operational management and supports the sustainable growth of Sun Computer Bali store.